Surface Pourbaix diagram of AgPd nanoalloys and its application in formate oxidation reaction. (1st August 2021) - Li, Zhen; Chen, Fuyi; Bian, Weiqi; Kou, Bo; Wang, Qiao; Guo, Longfei; Jin, Tao; Tang, Quan; Pan, Bowei
Highlights: Surface pourbaix diagrams for 38-atom AgPd nanoalloys with different Ag/Pd ratio are constructed based on the density functional theory. AgPd nanoalloys with a core–shell structure have an improved oxidation resistance compared with pure Ag or Pd nanoparticle. Ag18 Pd20 has an excellent durability against electrochemical dissolution and oxidation among all the calculated AgPd nanoalloys. The formate oxidation reaction performance of self-reconstructed Ag48 Pd52 nanoalloy increases due to the higher oxidation state of Ag atoms. Abstract: Surface Pourbaix diagrams for 38-atom AgPd nanoalloys with different Ag/Pd ratio are constructed based on the density functional theory calculations, with an increasing electrode potential, the adsorbed hydroxides increase on the surface of nanoparticle and convert to oxygen atoms partially sunk into subsurface. AgPd nanoalloys with a core-shell structure have an improved oxidation resistance compared with pure nanoparticle and Ag atoms on nanoalloys surface could suppress Pd dissolution and oxidation. It is newfound that a substitutional introduction of Pd atoms into the core of AgPd nanoalloys could suppress the oxide formations and increase the oxidation resistance, and a substitutional introduction of Ag atoms onto the surface of Pd38 nanoparticle could suppress Pd dissolution. Among all the calculated AgPd nanoalloys, Ag18 Pd20 has an excellent durability against electrochemical dissolution and oxidation. Experimentally, the activity of as-synthesized Ag48 Pd52 nanoalloy notably increases with increasing the upper limit potential from 0.3 to 0.5 V under cyclic voltammetry test of formate oxidation reaction (FOR). Increased oxidation state of Ag atoms on electrocatalyst surface, which is confirmed by Mulliken charge analysis, has been identified as the key to prompt the FOR activity enhancement. Graphical abstract: Image, graphical abstract Surface Pourbaix diagram predicts the surface phase transformations of Ag18 Pd20 nanoalloy at the potential ranges of the formate oxidation reaction (FOR), which could take place on the anode side of direct formate fuel cell. The Mulliken charge analysis on the surface oxides of Ag18 Pd20 indicates that the increase of oxidation state of Ag on the electrocatalyst surface has been identified as the key to prompt the FOR activity enhancement.